Glass-to-glass electrostatic bonding for FED tubeless packaging application - Ju, BK; Choi, WB; Lee, YH; Jung, SJ; Lee, NY; Han, JI; Cho, KI; Oh, MH (ELSEVIER ADVANCED TECHNOLOGY, 1998)
Two ITO-coated glass wafers (Corning #7740, #0080) are successfully bonded by the typical Si-Pyrex electrostatic bonding mechanism. Both Si=#7740 and Ti-(Li-doped SiO2) interlayer systems can be employed for the electrostatic bonding of #7059-#7059 and #0080-#0080 glass wafer pairs. This glass-to-glass electrostatic bonding process can be applied to the clean and tubeless packaging of field emission display panels. (C) 1998 Elsevier Science Ltd. All rights reserved.